Method for evaluating metal contamination in ion implanter and method for manufacturing ion implanted silicon wafer
The method accurately evaluates metal contamination in ion implanters by forming an amorphous region in the ion implantation layer and using acid cleaning to isolate implanter-specific impurities, resulting in reduced contamination and improved semiconductor device quality.
Patent Information
- Application Number
- JP2023153880
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2043-09-20
AI Technical Summary
Existing methods for evaluating metal contamination in ion implanters do not accurately measure the amount of metal impurities incorporated into the ion implantation layer, which affects semiconductor device characteristics, and can be influenced by environmental factors, leading to inaccurate assessments.
A method involving ion implantation, acid cleaning, and metal impurity measurement is employed, where the ion implantation forms an amorphous region in the ion implantation layer without reaching the silicon wafer surface, followed by acid washing to isolate and measure metal impurities originating from the ion implanter, using specific ion beam conditions and acid solutions.
This method allows for high-accuracy evaluation of metal contamination in ion implanters, producing ion-implanted silicon wafers with reduced contamination, thereby improving semiconductor device quality.
Smart Images

Figure 2025045871000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for evaluating metal contamination in an ion implanter and a method for manufacturing an ion-implanted silicon wafer. [Background technology]
[0002] Epitaxial silicon wafers, which have an epitaxial layer of single crystal silicon formed on a silicon wafer, are used as device substrates for fabricating various semiconductor devices, such as MOSFETs (Metal-Oxide-Semiconductor Field-Effect Transistors), DRAMs (Dynamic Random Access Memories), power transistors, and BSI (Back Side Illumination) type CISs (CMOS Image Sensors). Epitaxial silicon wafers are a core material in semiconductor devices and are indispensable in supporting our lives.
[0003] Among these, CIS is a core component of the camera function of digital cameras and smartphones, and is an essential technology for capturing images and videos. By producing high-quality epitaxial silicon wafers and providing high-quality, highly accurate images, CIS can contribute to sustainable activities, such as improving the quality and efficiency of medical care and improving the health and welfare of society as a whole (Sustainable Development Goal (SDG) Goal 3: "Ensure healthy lives and promote well-being for all at all ages") and improving social safety and security by suppressing crime and taking measures against disasters through the sophistication of surveillance and security systems (Sustainable Development Goal (SDG) Goal 11: "Make cities inclusive, safe, resilient and sustainable").
[0004] Here, if the epitaxial layer is contaminated with heavy metals, the dark current of the CIS increases, and defects called white defects occur, which are factors that degrade the characteristics of the semiconductor device. Therefore, in order to suppress such heavy metal contamination, there is a technology that forms gettering sites in the silicon wafer to capture heavy metals. One known method is to implant ions into the silicon wafer and then form the epitaxial layer. In this method, the ion-implanted layer formed on the surface of the silicon wafer functions as the gettering site.
[0005] Here, if metal impurities originating from the metal contamination of the ion implanter are introduced into the ion implantation layer of the silicon wafer, it will naturally cause deterioration of the characteristics of the semiconductor device formed in the epitaxial layer thereafter. The following two are considered as the main causes of metal contamination of the ion implantation layer originating from the metal contamination of the ion implanter. The first is that the inner wall of the chamber of the ion implanter is mainly composed of metal members, and the inner wall is sputtered by irradiating the inner wall of the chamber with an ion beam, and the scattered metal is physically adsorbed onto the surface of the silicon wafer. In this case, the metal attached to the surface of the silicon wafer is knocked on to the inside of the silicon wafer by collision with the implanted ions, resulting in metal contamination of the ion implantation layer. The second is that the ionized metal is contained in the ion beam and transported to the silicon wafer. In this case, too, metal ions are contained in the ion beam, causing metal contamination of the ion implantation layer.
[0006] Therefore, it is necessary to appropriately evaluate the degree of metal contamination (cleanliness) of an ion implanter and to manufacture ion-implanted silicon wafers as products using an ion implanter that has been confirmed to have a high level of cleanliness. Conventionally, the following methods for evaluating metal contamination of an ion implanter have been known.
[0007] Patent Document 1 describes a method for measuring the number of particles in a chamber of an ion implanter and grasping the level of metal contamination in the chamber based on the measured number of particles. Patent Document 2 describes "a metal contamination evaluation method for evaluating metal contamination due to ion implantation in a semiconductor manufacturing process, the method comprising an amorphous layer forming step of forming an amorphous layer on a wafer surface in advance, an ion implantation step of implanting ions to be evaluated from above the amorphous layer, a heat treatment step of heat treating the wafer after the ion implantation, and an SPV (Surface Photo Voltage) measurement step of measuring the contaminant metal content of the wafer after the heat treatment." [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 9-180668 [Patent Document 2] JP 2007-258602 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, the method described in Patent Document 1 grasps the level of metal contamination in the chamber based on the number of particles, and does not evaluate the metal contamination of the ion implanter based on the amount of metal impurities incorporated into the ion implantation layer, which may actually affect the characteristics of a semiconductor device. In addition, the method described in Patent Document 2 performs a heat treatment before the SPV measurement, so that metal contamination mixed into the ion implantation layer due to the heat treatment also affects the measurement result. For this reason, it is not possible to evaluate the level of metal contamination of the ion implanter with high accuracy.
[0010] In view of the above problems, the present invention aims to provide a method for evaluating metal contamination in an ion implanter, which is capable of evaluating with high accuracy the degree of metal contamination in an ion implanter that may affect the characteristics of a semiconductor device, and a method for producing ion-implanted silicon wafers, which is capable of producing ion-implanted silicon wafers with reduced metal contamination resulting from the metal contamination of the ion implanter. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors have conducted extensive research and obtained the following findings. When ions are implanted into a silicon wafer using an ion implanter, metal impurities originating from metal contamination of the ion implanter are introduced into the ion implantation layer formed on the surface layer of the silicon wafer in an amount corresponding to the level of metal contamination. By measuring the concentration of the metal impurities introduced into the ion implantation layer, the level of metal contamination of the ion implanter that may affect the characteristics of a semiconductor device can be evaluated. At this time, the metal impurities introduced into the inside of the ion implantation layer are exclusively originating from metal contamination of the ion implanter, whereas the metal impurities present on the surface of the silicon wafer (i.e., the surface of the ion implantation layer) include those originating from the metal contamination of the ion implanter as well as those originating from environmental factors such as the atmosphere in the installation environment of the ion implanter and the storage container of the silicon wafer. Therefore, if the ion implantation layer is simply subjected to measurement of the metal impurity concentration, the measured value will include contamination factors other than the ion implanter, and the level of metal contamination of the ion implanter cannot be evaluated with high accuracy. Therefore, after the ion implantation, the surface of the silicon wafer is acid washed to remove the metal impurities present on the surface of the silicon wafer, and then the ion-implanted layer is subjected to measurement of the metal impurity concentration, which makes it possible to measure the concentration of only the metal impurities originating from the metal contamination of the ion implanter.
[0012] Here, in recent years, the cleanliness of ion implantation equipment has been improved, and the amount of metal impurities introduced into the ion implantation layer is very small. Therefore, in order to evaluate such a small amount of metal contamination with high accuracy, it is necessary to increase the amount of metal impurities introduced into the ion implantation layer by increasing the dose of ions implanted into the silicon wafer, even if the cleanliness of the ion implantation machine is the same. Here, as the dose of ions increases, an amorphous region is formed in the ion implantation layer. That is, by performing ion implantation with a high dose such that a part of the ion implantation layer in the thickness direction becomes an amorphous region, the small amount of metal contamination of the ion implantation machine can be evaluated with high accuracy.
[0013] However, the inventors have studied and found that if the dose of ions is excessively increased and the amorphous region reaches the surface of the silicon wafer, the accuracy of the evaluation of metal contamination decreases. The inventors have examined the cause and found that when the amorphous region reaches the surface of the silicon wafer, the amount of damage to the surface of the silicon wafer is too large, and the surface of the silicon wafer becomes a hydrophilic surface instead of a hydrophobic surface, so that the metal impurities present on the surface of the silicon wafer cannot be completely removed in the acid cleaning process after ion implantation, that is, the influence of disturbances cannot be completely eliminated. Therefore, in order to evaluate trace metal contamination with high accuracy while eliminating the influence of disturbances, it is important to perform ion implantation under ion implantation conditions in which a part of the thickness direction of the ion implantation layer becomes an amorphous region and the amorphous region does not reach the surface of the silicon wafer.
[0014] The present invention, which has been completed based on the above findings, has the following essential features. [1] A step (A) of irradiating a surface of a silicon wafer with an ion beam emitted from an ion implanter to form an ion-implanted layer in a surface layer portion of the silicon wafer in which constituent elements of the ion beam are dissolved, and introducing metal impurities originating from metal contamination of the ion implanter into the ion-implanted layer; Then, a step (B) of acid-cleaning the surface of the silicon wafer; Then, a step (C) of measuring the concentration of the metal impurities introduced into the ion-implanted layer; Then, a step (D) of evaluating the degree of metal contamination of the ion implanter based on the measured concentration of the metal impurities; having the step (A) is performed under ion implantation conditions in which a part of the ion-implanted layer in a thickness direction becomes an amorphous region, and the amorphous region does not reach a surface of the silicon wafer.
[0015] [2] The method for evaluating metal contamination of an ion implanter according to the above [1], wherein the step (A) is carried out under ion implantation conditions such that the scattering intensity on the surface of the silicon wafer measured using a UV laser having a wavelength of 355 nm is 0.10 ppm or more and 0.35 ppm or less.
[0016] [3] The method for evaluating metal contamination of an ion implanter according to the above [1] or [2], wherein the ion beam is made of cluster ions containing carbon and hydrogen as the constituent elements.
[0017] [4] The method for evaluating metal contamination of an ion implanter according to any one of the above [1] to [3], wherein in the step (B), cleaning is performed with an acid solution or an acid solution containing an oxidizing agent.
[0018] [5] The method for evaluating metal contamination of an ion implanter according to the above [4], wherein the acid solution is one or more selected from the group consisting of hydrofluoric acid, a mixture of hydrofluoric acid and ammonium fluoride, hydrochloric acid, and dilute sulfuric acid, and the oxidizing agent is one or more selected from the group consisting of hydrogen peroxide, nitric acid, and ozone.
[0019] [6] The step (C) removing the ion-implanted layer by vapor-phase etching and allowing the metal impurities introduced into the ion-implanted layer to remain on the exposed surface of the silicon wafer by the vapor-phase etching; thereafter, contacting an acid solution with the surface of the silicon wafer exposed by the vapor phase etching to dissolve the metal impurities remaining on the exposed surface in the acid solution; Thereafter, measuring the concentration of the metal impurities in the acid solution; The method for evaluating metal contamination of an ion implanter according to any one of the above [1] to [5],
[0020] [7] The method for evaluating metal contamination in an ion implanter according to the above [6], further comprising measuring a thickness of the ion-implanted layer and determining an etching amount by the vapor-phase etching based on the measured thickness.
[0021] [8] The method for evaluating metal contamination of an ion implanter according to the above [7], wherein the thickness of the ion-implanted layer is determined by measuring a concentration profile of the constituent elements in a depth direction from the surface of the silicon wafer by SIMS.
[0022] [9] The method for evaluating metal contamination of an ion implanter according to any one of the above [1] to [8], wherein the metal impurities are one or more selected from the group consisting of Al, Ni, Fe, Cr, and Ti.
[0023]
[10] A method for producing ion-implanted silicon wafers, comprising the step of implanting ions into product silicon wafers using an ion implanter that has been evaluated as having a low level of metal contamination in step (D) by using the method for evaluating metal contamination of an ion implanter as described in any one of the above items [1] to [9], and the concentration of the metal impurities measured in step (C) being below a lower detection limit. Effect of the Invention
[0024] According to the method for evaluating metal contamination in an ion implanter of the present invention, it is possible to evaluate with high accuracy the degree of metal contamination in an ion implanter that may affect the characteristics of a semiconductor device. According to the method for producing an ion-implanted silicon wafer of the present invention, it is possible to produce an ion-implanted silicon wafer with reduced metal contamination originating from the metal contamination in the ion implanter. [Brief description of the drawings]
[0025] [Figure 1] 1 is a flow diagram showing the steps of a method for evaluating metal contamination of an ion implanter according to an embodiment of the present invention. [Diagram 2] 1A to 1C are cross-sectional views of a silicon wafer, each showing a schematic state of the silicon wafer in steps (A) to (C) of a method for evaluating metal contamination of an ion implanter according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing the relationship between the carbon dose when implanting C3H5 cluster ions and C5H5 cluster ions in Experimental Example 1 and the scattering intensity on the surface of a silicon wafer after implantation. [Figure 4] These are cross-sectional TEM images of the surface layer (ion-implanted layer) of a silicon wafer after implantation of C3H5 cluster ions in Experimental Example 1, where (A) is a case where the carbon dose is 2×1015 atoms / cm2, (B) is a case where the carbon dose is 3×1015 atoms / cm2, and (C) is a case where the carbon dose is 1×1016 atoms / cm2. [Diagram 5] 11 is a graph showing the relationship between the scattering intensity on the surface of a silicon wafer after implantation of C3H5 cluster ions and the Al concentration level of an ion-implanted layer in Experimental Example 2. [Figure 6] 13 is a graph showing the Al concentration levels of the ion-implanted layer in an example (ion implantation conditions in which the amorphous region does not reach the surface of the silicon wafer) and a comparative example (ion implantation conditions in which the amorphous region reaches the surface of the silicon wafer) in Experimental Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] (Method for evaluating metal contamination in ion implanters) 1 and 2, a method for evaluating metal contamination of an ion implanter according to one embodiment of the present invention includes, in this order, an ion implantation step (A), an acid cleaning step (B), a metal impurity measurement step (C), and a metal contamination evaluation step (D). In this embodiment, the metal impurity measurement step (C) includes, in this order, a vapor phase etching step (C-1), a metal impurity recovery step (C-2) using an acid solution, and a metal impurity concentration measurement step (C-3) in the acid solution.
[0027] [Ion implantation process (A)] In the ion implantation step (A), an ion beam emitted from an ion implanter is irradiated onto the surface of the silicon wafer 10 to form an ion implantation layer 12 in which the constituent elements of the ion beam are dissolved in a solid solution in the surface layer of the silicon wafer 10. At this time, metal impurities originating from metal contamination of the ion implanter are introduced into the ion implantation layer 12. With reference to FIG. 2, the outermost surface layer of the silicon wafer 10 is composed of a natural oxide film 16 having a thickness of about 5 to 15 Å. The metal impurities introduced into the inside of the ion implantation layer 12 are mainly originating from metal contamination of the ion implanter, whereas the metal impurities present together with the natural oxide film 16 on the surface of the silicon wafer 10 (i.e., the surface of the ion implantation layer 12) include those originating from metal contamination of the ion implanter as well as those originating from environmental factors such as the atmosphere in the installation environment of the ion implanter and a storage container for the silicon wafer.
[0028] The ion implanter may be any known or arbitrary one capable of implanting ions into the silicon wafer 10. For example, an example of a cluster ion implanter is CLARIS (registered trademark) manufactured by Nissin Ion Equipment Co., Ltd. The metal impurities causing metal contamination of the ion implanter may be one or more selected from the group consisting of Al, Ni, Fe, Cr, and Ti. The inner walls of each device (chamber, etc.) constituting the ion implanter are mainly made of aluminum alloy members or stainless steel (SUS) members. Therefore, Al, Ti, etc. scattered from the aluminum alloy members and Fe, Cr, Ni, etc. scattered from the SUS members cause metal contamination.
[0029] The silicon wafer 10 may be, for example, a bulk single crystal silicon wafer that does not have an epitaxial layer on the surface to be irradiated. Such a single crystal silicon wafer can be obtained by slicing a single crystal silicon ingot grown by the Czochralski method (CZ method) or the floating zone melting method (FZ method) with a wire saw or the like. In order to obtain a higher gettering ability, carbon and / or nitrogen may be added to the silicon wafer 10. Furthermore, any dopant may be added to the silicon wafer 10 at a predetermined concentration to make it n-type or p-type.
[0030] The ion beam emitted from the ion implanter may be made up of either monomer ions or cluster ions.
[0031] In one embodiment, the ion beam may be composed of cluster ions containing carbon and hydrogen as constituent elements. The "cluster ions" in this specification are obtained by bombarding gaseous molecules with electrons to dissociate the bonds of the gaseous molecules to form atomic aggregates of various numbers of atoms, fragmenting the atomic aggregates to ionize them, and performing mass separation of the ionized atomic aggregates of various numbers of atoms to extract ionized atomic aggregates of specific mass numbers. That is, the "cluster ions" in this specification are ionized clusters formed by aggregating a plurality of atoms into a mass by giving them a positive or negative charge, and are clearly distinguished from monoatomic ions such as carbon ions and monomolecular ions such as carbon monoxide ions. The number of constituent atoms of a cluster ion is usually about 5 to 100. As a cluster ion implantation device using such a principle, the above-mentioned CLARIS (registered trademark) manufactured by Nissin Ion Equipment Co., Ltd. can be used.
[0032] When the silicon wafer 10 is irradiated with cluster ions containing carbon and hydrogen, the silicon instantaneously reaches a high temperature of about 1350 to 1400°C due to the irradiation energy, and melts. After that, the silicon is rapidly cooled, and carbon and hydrogen are dissolved in the silicon wafer near the surface. That is, the "ion-implanted layer" in this specification means a layer in which carbon and hydrogen, which are constituent elements of the irradiated cluster ions, are dissolved in interstitial positions or substitution positions of the crystals in the surface layer of the silicon wafer. The ion-implanted layer is specified as a region in which the concentration of at least one element is detected to be higher than the background in the concentration profile of carbon and hydrogen in the depth direction of the silicon wafer. Immediately after the implantation of the cluster ions, the surface layer of the silicon wafer is generally 500 nm or less from the surface.
[0033] The conditions for irradiating the cluster ions include the cluster size, the dose amount, the acceleration voltage, and the beam current value.
[0034] The cluster size can be appropriately set to 2 to 100, preferably 60 or less, more preferably 50 or less. In this specification, "cluster size" means the number of atoms constituting one cluster. The cluster size can be adjusted by adjusting the pressure of the gas ejected from the nozzle, the pressure of the vacuum vessel, the voltage applied to the filament during ionization, etc. The cluster size can be determined by determining the cluster number distribution by mass spectrometry using a quadrupole high-frequency electric field or time-of-flight mass spectrometry, and calculating the average value of the cluster numbers.
[0035] The constituent elements of the cluster ion are not particularly limited as long as they contain carbon and hydrogen, but as an example, they are made of carbon and hydrogen. The constituent elements of the cluster ion may also contain elements other than hydrogen and carbon. For example, the constituent elements of the cluster ion may contain, in addition to hydrogen and carbon, one or more elements selected from the group consisting of boron, phosphorus, arsenic, and antimony.
[0036] The gaseous molecules that are the source of cluster ions are not particularly limited as long as they can produce cluster ions of the desired size. For example, cyclohexane (C6H 12 ) as the source gas, cluster ions consisting of carbon and hydrogen can be generated and extracted. In addition, pyrene (C 16 H 10 ), dibenzyl (C 14 H 14 ) Cluster C generated from n H m (3≦n≦16, 3≦m≦10, n and m are both integers) is preferably used because it is easy to control a small-sized cluster ion beam.
[0037] The dose of the cluster ions can be adjusted by controlling the ion irradiation time. The dose of each element constituting the cluster ions depends on the cluster ion species (cluster size) and the dose of the cluster ions (ions / cm 2 ) Therefore, the dose of the cluster ions may be appropriately set according to the type of cluster ions so that the dose of each element is a desired value. Usually, the dose of carbon is 1.0×10 14 atoms / cm 2 Above 1.0×10 16 atoms / cm 2 The preferred carbon dose is described below.
[0038] The acceleration voltage of the cluster ions, together with the cluster size, affects the peak position of the concentration profile of the constituent elements in the ion-implanted layer in the depth direction. In this embodiment, the acceleration voltage of the cluster ions can be set to more than 0 keV / Cluster and less than 200 keV / Cluster, preferably 100 keV / Cluster or less, and more preferably 80 keV / Cluster or less. Two methods are generally used to adjust the acceleration voltage: (1) electrostatic acceleration and (2) radio-frequency acceleration. The former method is a method in which a plurality of electrodes are arranged at equal intervals and equal voltages are applied between them to create a uniform acceleration electric field in the axial direction. The latter method is a linear linac method in which ions are accelerated using radio frequency while running in a straight line.
[0039] The beam current value of the cluster ions is not particularly limited, but is preferably determined appropriately from the range of 50 μA to 5000 μA. The beam current value of the cluster ions can be adjusted, for example, by changing the decomposition conditions of the raw material gas in the ion source.
[0040] In one embodiment, the ion beam may be composed of monomer ions. When, for example, monomer ions of carbon are implanted into the silicon wafer 10, the monomer ions repel the silicon atoms constituting the silicon wafer and are implanted at a predetermined depth in the silicon wafer 10. The implantation depth depends on the type of constituent element of the implanted ions and the acceleration voltage of the ions. In this case, the carbon concentration profile in the depth direction of the silicon wafer becomes relatively broad, and the thickness of the region where the carbon concentration is detected to be higher than the background (i.e., the ion-implanted layer 12) is approximately 0.5 to 1 μm. Examples of elements implanted by monomer ions include carbon, boron, phosphorus, and arsenic. Usually, the dose of carbon is 1.0×10 14 atoms / cm 2 Above 1.0×10 16 atoms / cm 2The accelerating voltage of the monomer ions is generally set to 150 to 2000 keV / atom, and may be set appropriately within this range.
[0041] [Acid washing process (B)] In the acid cleaning step (B), the surface of the silicon wafer 10 is acid-cleaned. With reference to Fig. 2, the acid cleaning step (B) removes metal impurities present on the surface of the silicon wafer 10 together with the native oxide film 16. This makes it possible to measure the concentration of only the metal impurities originating from metal contamination in the ion implanter in the subsequent step (C).
[0042] The acid solution used for the acid cleaning is not particularly limited as long as it can remove metal impurities present on the surface of the silicon wafer 10, and may be an acid solution alone or an acid solution containing an oxidizing agent. Examples of the acid solution include hydrofluoric acid (aqueous solution of hydrogen fluoride (HF)), a mixture of hydrofluoric acid and ammonium fluoride (NH4F) (buffered hydrofluoric acid), hydrochloric acid (aqueous solution of hydrogen chloride (HCl)), and dilute sulfuric acid (aqueous solution of sulfuric acid (H2SO4)). One or more of these may be used. Examples of the oxidizing agent include hydrogen peroxide (H2O2), nitric acid (HNO3), and ozone (O3). One or more of these may be used.
[0043] Particularly preferred acid solutions include hydrofluoric acid, buffered hydrofluoric acid, hydrofluoric acid with added hydrogen peroxide (H2O2), hydrochloric acid with added hydrogen peroxide (H2O2), and dilute sulfuric acid with added hydrogen peroxide (H2O2).
[0044] The method of acid cleaning is not particularly limited, and may be a method of immersing the silicon wafer 10 in an acid solution or a method of spin-cleaning the silicon wafer 10 with an acid solution.
[0045] The etching depth by the acid cleaning is preferably such that the native oxide film 16 is removed, and may be, for example, about 5 to 15 Å.
[0046] [Metal impurity measurement process (C)] Step (C) measures the concentration of the metal impurities introduced into the ion-implanted layer 12. In this embodiment, the metal impurity measurement step (C) includes, in this order, a vapor-phase etching step (C-1), a metal impurity recovery step (C-2) using an acid solution, and a metal impurity concentration measurement step (C-3) in the acid solution.
[0047] 2, in the vapor-phase etching step (C-1), the ion-implanted layer 12 is removed by vapor-phase etching, and the metal impurities introduced into the ion-implanted layer 12 are left on the exposed surface of the silicon wafer 10 by the vapor-phase etching. Here, since the metal impurities present on the surface of the silicon wafer 10, including contamination factors other than the ion implanter, are removed by the acid cleaning step (B), the metal impurities remaining on the exposed surface of the silicon wafer 10 after the vapor-phase etching were introduced into the ion-implanted layer 12 and originate solely from metal contamination of the ion implanter.
[0048] The vapor phase etching can be performed by a known vapor phase decomposition method (VPD). The etching gas includes hydrogen fluoride (HF) gas and nitric acid (HNO3) gas. The etching gas including these gases can be generated, for example, by heating and volatilizing an aqueous solution including hydrofluoric acid and nitric acid. The vapor phase etching can be performed in a sealed container. Specifically, the aqueous solution and the silicon wafer are placed in the sealed container without contacting each other, and the aqueous solution in the sealed container is heated by a heater attached to the sealed container to generate the etching gas. This allows the etching gas to come into contact with the surface of the silicon wafer.
[0049] The amount of etching by vapor-phase etching can be controlled by the etching time (contact time with gas), and is preferably set so as to remove the ion-implanted layer 12 located in the surface portion of the silicon wafer 10. The amount of etching can be set within a range of 1 μm to 10 μm from the surface of the silicon wafer 10, for example.
[0050] From the viewpoint of reliably removing the ion-implanted layer 12 without increasing the process time, it is preferable to measure the thickness of the ion-implanted layer 12 and determine the amount of etching by vapor-phase etching based on the obtained measured value.
[0051] The thickness of the ion-implanted layer 12 can be obtained by measuring, by secondary ion mass spectrometry (SIMS), the concentration profile of the constituent elements of the ions in the depth direction from the surface of the silicon wafer 10. The ion-implanted layer is identified as a region in which the concentration of at least one element is detected to be higher than the background in the concentration profile of the constituent elements of the ions in the depth direction of the silicon wafer.
[0052] Next, in the metal impurity recovery process (C-2) using an acid solution, an acid solution is brought into contact with the exposed surface of the silicon wafer 10 by vapor-phase etching, and the metal impurities remaining on the exposed surface are dissolved in the acid solution. The acid solution used here is not particularly limited as long as it can dissolve the metal impurities, and may be an acid solution alone or an acid solution containing an oxidizing agent. Examples of the acid solution include hydrofluoric acid and hydrochloric acid, and one or more of these can be used. Examples of the oxidizing agent include hydrogen peroxide (H2O2), nitric acid (HNO3), and one or more of these can be used. Particularly desirable acid solutions include hydrofluoric acid, hydrofluoric acid with added hydrogen peroxide (H2O2), and hydrochloric acid with added hydrogen peroxide (H2O2).
[0053] The manner in which the acid solution is brought into contact with the exposed surface of the silicon wafer 10 is not particularly limited, but from the viewpoint of analytical accuracy, it is preferable to bring a wide range of the exposed surface of the silicon wafer 10 into contact with the acid solution. Since the exposed surface of the silicon wafer 10 is hydrophobicized by vapor-phase etching, when the acid solution is dropped, the acid solution maintains a droplet state without spreading. Therefore, by dropping the acid solution onto the exposed surface of the silicon wafer 10 and moving the formed droplets on the exposed surface, metal impurities can be collected from a wide range of the exposed surface. The moving method is not particularly limited, and for example, the droplets can be moved in a spiral shape from the edge of the silicon wafer toward the center.
[0054] Next, in the step (C-3) of measuring the concentration of metal impurities in the acid solution, the acid solution is recovered from the exposed surface of the silicon wafer, and the concentration of metal impurities in the recovered acid solution is measured. The concentration of metal impurities can be measured by chemical analysis such as inductively coupled plasma mass spectrometry (ICP-MS) or atomic absorption spectrometry (AAS).
[0055] [Metal contamination evaluation process (D)] Next, in the metal contamination evaluation step (D), the degree of metal contamination of the ion implanter is evaluated based on the concentration of the metal impurities measured in step (C). Specifically, when the concentration of the metal impurities measured in step (C) is below the lower detection limit, the ion implanter can be evaluated to have a low level of metal contamination and a high level of cleanliness. In this case, the ion implanter can be used to inject ions into product silicon wafers to produce ion-implanted silicon wafers. On the other hand, when the concentration of the metal impurities measured in step (C) is equal to or higher than the lower detection limit, the ion implanter can be evaluated to have a high level of metal contamination and a low level of cleanliness. In this case, the ion implanter is not used to produce product ion-implanted silicon wafers.
[0056] For example, immediately after maintenance (overhaul) of the ion implanter, outside air is introduced into the chamber due to the maintenance, resulting in a low degree of cleanliness. In this case, the cleanliness of the ion implanter can be improved by performing so-called blank shots once or twice or more, in which ions are implanted into a dummy wafer that will not become a product. Thus, after each blank shot performed after maintenance, a cleanliness evaluation of the ion implanter according to this embodiment is performed, and it is confirmed that the concentration of metal impurities measured in step (C) is below the lower detection limit, and then the ion implanter can be used to manufacture ion-implanted silicon wafers for product use.
[0057] [Ion implantation conditions] 2, in this embodiment, it is essential that the ion implantation step (A) is performed under ion implantation conditions in which a part of the ion implanted layer 12 in the thickness direction becomes an amorphous region 14 and the amorphous region 14 does not reach the surface of the silicon wafer 10. This makes it possible to evaluate with high accuracy the degree of metal contamination of the ion implanter that may affect the characteristics of a semiconductor device.
[0058] By implanting ions at a high dose such that a portion of the ion implantation layer 12 in the thickness direction becomes an amorphous region 14, it is possible to increase the amount of metal impurities introduced into the ion implantation layer 12 even if the cleanliness of the ion implantation machine is the same. This makes it possible to evaluate trace metal contamination of the ion implantation machine with high accuracy.
[0059] On the other hand, if the ion dose is excessively increased and the amorphous region reaches the surface of the silicon wafer, the accuracy of the metal contamination evaluation decreases. This is presumably because, when the amorphous region reaches the surface of the silicon wafer, the amount of damage to the surface of the silicon wafer is too large, and the surface of the silicon wafer becomes hydrophilic rather than hydrophobic, so that the metal impurities present on the surface of the silicon wafer cannot be completely removed in the acid cleaning process (B) after ion implantation, that is, the influence of disturbances cannot be completely eliminated. Therefore, in order to eliminate the influence of disturbances, it is important to set the dose so that the amorphous region 14 does not reach the surface of the silicon wafer 10.
[0060] Whether or not an amorphous region 14 is generated in the ion-implanted layer 12 and whether or not the amorphous region 14 reaches the surface of the silicon wafer 10 can be determined from a cross-sectional TEM image of the surface layer portion (ion-implanted layer 12) of the silicon wafer 10 after ion implantation. With reference to FIGS. 4(A) to (C), the white parts are amorphous regions, and the black parts are crystalline regions. When the white parts reach the surface of the silicon wafer as in FIG. 4(C), it is determined that the amorphous regions reach the surface of the silicon wafer. When there are black parts on the white parts and the black parts make up the surface of the silicon wafer as in FIGS. 4(A) and (B), it is determined that the amorphous regions do not reach the surface of the silicon wafer.
[0061] The present inventors have found that there is a correlation between the degree of amorphization of the ion-implanted layer 12 and the scattering intensity at the surface of the silicon wafer 10 measured using a UV laser with a wavelength of 355 nm. When the dose is low and no amorphous region 14 is generated in the ion-implanted layer 12, the scattering intensity is less than 0.10 ppm. When the dose is increased and the amorphous region 14 is generated in the ion-implanted layer 12, the scattering intensity becomes 0.10 ppm or more. As the dose is increased and the amorphization of the ion-implanted layer 12 progresses, the scattering intensity becomes higher, exceeding 0.30 ppm and reaching a level of 0.35 or less. However, when the amorphous region 14 reaches the surface of the silicon wafer 10, the scattering intensity drops sharply and becomes less than 0.10 ppm. Therefore, it is preferable that the ion implantation step (A) is performed under ion implantation conditions that result in the scattering intensity being 0.10 ppm or more and 0.35 ppm or less. The range of the scattering intensity is more preferably 0.15 ppm or more and 0.35 ppm or less, even more preferably 0.25 ppm or more and 0.35 ppm or less, and most preferably 0.30 ppm or more and 0.35 ppm or less.
[0062] "Scattering intensity" is defined as the signal obtained by focusing scattered light detected in a wide channel using, for example, a KLA-Tencor surface inspection device, Surfscan SP-2, in normal mode, where a UV laser with a wavelength of 355 nm is incident perpendicularly on the surface of a silicon wafer.
[0063] The degree of amorphization of the ion-implanted layer 12 and the scattering intensity depend on the type and dose of the implanted ions (mainly the carbon dose when the constituent elements of the ions include carbon). Details will be described in the examples below, but the range of doses in which the amorphous region satisfies the conditions of the present invention, that is, the range of doses in which the scattering intensity is 0.10 ppm or more and 0.35 ppm or less, varies depending on the type of ions implanted.
[0064] (Method of manufacturing ion-implanted silicon wafers) The method for producing an ion-implanted silicon wafer according to one embodiment of the present invention uses the method for evaluating metal contamination in an ion implanter according to one embodiment of the present invention, and implants ions into a product silicon wafer using an ion implanter that has been evaluated as having a low level of metal contamination in step (D) by measuring the concentration of metal impurities below the lower detection limit in step (C). This makes it possible to produce ion-implanted silicon wafers with reduced metal contamination originating from the metal contamination of the ion implanter. EXAMPLES
[0065] (Experimental Example 1) An n-type silicon wafer (diameter: 300 mm, thickness: 775 μm, dopant type: phosphorus, resistivity: 10 Ω cm) obtained from a CZ single crystal silicon ingot was prepared. Next, a cluster ion generator (manufactured by Nissin Ion Equipment Co., Ltd., CLARIS (registered trademark)) was used to generate cyclohexane (CH 12 ) was used to generate and extract C3H5 cluster ions, and an ion implantation process was carried out in which the surface of a silicon wafer was irradiated with the irradiation conditions of an acceleration voltage of 80 keV / Cluster and a beam current value of 850 μA. The dose of the cluster ions was 1×10 14 atoms / cm 2 From 1×10 16 atoms / cm 2 The conditions were set to be within the range of 12.
[0066] In addition, C5H5 cluster ions were used instead of C3H5 cluster ions, and the carbon dose was 1×10 14 atoms / cm 2 From 2.5 × 10 15 atoms / cm 2 The same ion implantation process as described above was carried out, except that the nine conditions were set within the range from 1 to 9.
[0067] The carbon and hydrogen concentration profiles in the depth direction from the surface of the silicon wafer after ion implantation were measured by SIMS. An ion-implanted layer was identified at a depth of approximately 400 nm from the surface of the silicon wafer, although this differed depending on the ion species and carbon dose.
[0068] The scattering intensity of the silicon wafers implanted with ions under each condition was measured by the method described above using a surface inspection device, Surfscan SP-2, manufactured by KLA-Tencor. The results are shown in Figure 3. The silicon wafers implanted with ions under each condition were also observed with a transmission electron microscope (TEM). Representatively, C3H5 cluster ions were used, and a carbon dose of 2 x 10 15 atoms / cm 2 , 3×10 15 atoms / cm 2 , 1×10 16 atoms / cm 2 Cross-sectional TEM images of the surface layer (ion-implanted layer) of the silicon wafer for the three conditions are shown in FIGS. 4(A) to (C).
[0069] As can be seen from Figs. 3 and 4, when using C3H5 cluster ions, the carbon dose was 2 × 10 15 atoms / cm 2 At a carbon dose of 1×10, the amorphous region begins to form and the scattering intensity becomes 0.10 or more. As the carbon dose increases, the ratio of the amorphous region in the ion-implanted layer increases and the scattering intensity also increases. 16 atoms / cm 2 At this dose, the amorphous region reached the surface of the silicon wafer, and the scattering intensity dropped sharply to a level of less than 0.10 ppm. This tendency was also observed when C5H5 cluster ions were used. However, the range of carbon doses at which an amorphous region was formed in an area that did not reach the surface of the silicon wafer was different from that when C3H5 cluster ions were used.
[0070] (Experimental Example 2) An n-type silicon wafer (diameter: 300 mm, thickness: 775 μm, dopant type: phosphorus, resistivity: 10 Ω cm) obtained from a CZ single crystal silicon ingot was prepared. Next, a cluster ion generator (manufactured by Nissin Ion Equipment Co., Ltd., CLARIS (registered trademark)) was used to generate cyclohexane (CH 12 ) was used to generate and extract C3H5 cluster ions, and an ion implantation process was carried out in which the surface of a silicon wafer was irradiated with the following irradiation conditions: acceleration voltage 80 keV / Cluster, beam current value 850 μA. The dose of the cluster ions was 2×10 14 atoms / cm 2 From 5×10 15 atoms / cm 2 The ion implanter used for each condition was in a state where the level of metal contamination was high immediately after maintenance, and the level of metal contamination under each condition was set to be the same.
[0071] For the silicon wafers implanted with ions under each condition, the scattering intensity was measured using the method described above, using a surface inspection device, Surfscan SP-2, manufactured by KLA-Tencor. The results are shown in Figure 5. TEM images confirmed that under the two conditions where the scattering intensity was less than 0.10 ppm, no amorphous region was formed, whereas under the four conditions where the scattering intensity was 0.10 ppm or more, an amorphous region was formed in the ion-implanted layer that did not reach the surface of the silicon wafer.
[0072] The silicon wafers implanted under each condition were subjected to an acid cleaning process. That is, the silicon wafer surface was cleaned (immersed) using an acid solution of 0.5 mass% hydrofluoric acid with 2 mass% hydrogen peroxide (H2O2) added. The etching depth by the acid cleaning was about 5 Å, and the native oxide film was removed as well as metal impurities present on the surface of the silicon wafer.
[0073] After that, a surface layer (including an ion-implanted layer) of about 5 μm was removed from the surface of the silicon wafer by a vapor-phase etching process. The etching gas was generated by heating and volatilizing an aqueous solution containing hydrofluoric acid and nitric acid. Then, an acid solution containing 2 mass% hydrofluoric acid and 2 mass% hydrogen peroxide (H2O2) was contacted with the exposed surface of the silicon wafer by the vapor-phase etching, and the metal impurities remaining on the exposed surface were dissolved in the acid solution. Specifically, the acid solution was dropped on the exposed surface of the silicon wafer, and the formed droplets were moved on the exposed surface to collect the metal impurities from a wide range of the exposed surface. Next, the acid solution was collected from the exposed surface of the silicon wafer, and the aluminum concentration in the collected acid solution was measured by ICP-MS. The results are shown in Figure 5.
[0074] As can be seen from FIG. 5, aluminum was not detected under two conditions where the dose was low and the scattering intensity was less than 0.10 ppm, but aluminum was detected under four conditions where the dose was high and the scattering intensity was 0.10 ppm or more and 0.35 ppm or less.
[0075] (Experimental Example 3) An n-type silicon wafer (diameter: 300 mm, thickness: 775 μm, dopant type: phosphorus, resistivity: 10 Ω cm) obtained from a CZ single crystal silicon ingot was prepared. Next, a cluster ion generator (manufactured by Nissin Ion Equipment Co., Ltd., CLARIS (registered trademark)) was used to generate cyclohexane (CH 12 ) was used to generate and extract C3H5 cluster ions, and an ion implantation process was carried out in which the surface of a silicon wafer was irradiated with the following irradiation conditions: acceleration voltage 80 keV / Cluster, beam current value 850 μA. The dose of the cluster ions was 3×10 15 atoms / cm 2 (Example of invention) and 1×10 16 atoms / cm 2The conditions were set to satisfy two conditions, (1) and (2) (Comparative Example). In this Experimental Example 3, ion implantation was performed four times, from the first run to the fourth run, after the maintenance of the ion implanter. The state immediately after the maintenance was one with a high level of metal contamination, and the state in the fourth run was one with a low level of metal contamination (high cleanliness).
[0076] The scattering intensity of the silicon wafers implanted under each condition was measured by the above-mentioned method using a surface inspection device Surfscan SP-2 manufactured by KLA-Tencor. The scattering intensity was 0.32 ppm in the inventive example and 0.08 ppm in the comparative example. In addition, it was confirmed by TEM images that an amorphous region that did not reach the surface of the silicon wafer was formed in the ion-implanted layer in the inventive example, while the amorphous region reached the surface of the silicon wafer in the comparative example.
[0077] The silicon wafers implanted under each condition were subjected to an acid cleaning process. That is, the silicon wafer surface was cleaned (immersed) using an acid solution of 0.5 mass% hydrofluoric acid with 2 mass% hydrogen peroxide (H2O2) added. The etching depth by the acid cleaning was about 5 Å, and the native oxide film was removed as well as metal impurities present on the surface of the silicon wafer.
[0078] After that, a surface layer (including an ion-implanted layer) of about 5 μm was removed from the surface of the silicon wafer by a vapor-phase etching process. The etching gas was generated by heating and volatilizing an aqueous solution containing hydrofluoric acid and nitric acid. Then, an acid solution containing 2 mass% hydrofluoric acid and 2 mass% hydrogen peroxide (H2O2) was contacted with the exposed surface of the silicon wafer by the vapor-phase etching, and the metal impurities remaining on the exposed surface were dissolved in the acid solution. Specifically, the acid solution was dropped on the exposed surface of the silicon wafer, and the formed droplets were moved on the exposed surface to collect the metal impurities from a wide range of the exposed surface. Next, the acid solution was collected from the exposed surface of the silicon wafer, and the aluminum concentration in the collected acid solution was measured by ICP-MS. The results are shown in Figure 6.
[0079] Typically, metal contamination inside an ion implanter is highest after maintenance and decreases as the number of implantation runs increases. In the comparative example, the amount of detected Al is high, but it can be seen that there is almost no change in the Al concentration, regardless of the number of runs after maintenance. This is because in the comparative example, the surface of the silicon wafer became amorphous, and the metal impurities present on the surface of the silicon wafer could not be sufficiently removed by the acid cleaning process, which caused disturbances in the analysis results. In contrast, in the example of the invention, the amount of detected Al decreases as the number of runs increases, indicating that metal contamination caused by ion implantation was detected with high sensitivity. [Industrial Applicability]
[0080] According to the method for evaluating metal contamination in an ion implanter of the present invention, it is possible to evaluate with high accuracy the degree of metal contamination in an ion implanter that may affect the characteristics of a semiconductor device. According to the method for producing an ion-implanted silicon wafer of the present invention, it is possible to produce an ion-implanted silicon wafer with reduced metal contamination originating from the metal contamination in the ion implanter. [Explanation of symbols]
[0081] 10. Silicon Wafers 12 Ion implantation layer 14 Amorphous region 16 Native oxide film
Claims
1. A process (A) of irradiating a surface of a silicon wafer with an ion beam emitted from an ion implanter to form an ion-implanted layer in which constituent elements of the ion beam are dissolved in a solid solution in a surface layer portion of the silicon wafer, and introducing metal impurities derived from metal contamination of the ion implanter into the ion-implanted layer; Then, a step (B) of acid-cleaning the surface of the silicon wafer; Then, a step (C) of measuring the concentration of the metal impurities introduced into the ion-implanted layer; Then, a step (D) of evaluating the degree of metal contamination of the ion implanter based on the measured concentration of the metal impurities; having the step (A) is performed under ion implantation conditions in which a part of the ion-implanted layer in a thickness direction becomes an amorphous region, and the amorphous region does not reach a surface of the silicon wafer.
2. 2. The method for evaluating metal contamination in an ion implanter according to claim 1, wherein the step (A) is performed under ion implantation conditions such that a scattering intensity on the surface of the silicon wafer measured using a UV laser having a wavelength of 355 nm is 0.10 ppm or more and 0.35 ppm or less.
3. 2. The method for evaluating metal contamination in an ion implanter according to claim 1, wherein the ion beam is made up of cluster ions containing carbon and hydrogen as the constituent elements.
4. 2. The method for evaluating metal contamination of an ion implanter according to claim 1, wherein in the step (B), cleaning is performed with an acid solution or an acid solution containing an oxidizing agent.
5. 5. The method for evaluating metal contamination of an ion implanter according to claim 4, wherein the acid solution is one or more selected from the group consisting of hydrofluoric acid, a mixture of hydrofluoric acid and ammonium fluoride, hydrochloric acid, and dilute sulfuric acid, and the oxidizing agent is one or more selected from the group consisting of hydrogen peroxide, nitric acid, and ozone.
6. The step (C) removing the ion-implanted layer by vapor-phase etching and allowing the metal impurities introduced into the ion-implanted layer to remain on the exposed surface of the silicon wafer by the vapor-phase etching; thereafter, contacting an acid solution with the surface of the silicon wafer exposed by the vapor phase etching to dissolve the metal impurities remaining on the exposed surface in the acid solution; Thereafter, measuring the concentration of the metal impurities in the acid solution; The method for evaluating metal contamination of an ion implanter according to claim 1 , comprising:
7. 7. The method for evaluating metal contamination in an ion implanter according to claim 6, further comprising the steps of: measuring a thickness of the ion-implanted layer; and determining an etching amount by the vapor-phase etching based on the measured thickness.
8. 8. The method for evaluating metal contamination of an ion implanter according to claim 7, wherein the thickness of the ion-implanted layer is determined by measuring a concentration profile of the constituent elements in a depth direction from the surface of the silicon wafer by SIMS.
9. 2. The method for evaluating metal contamination of an ion implanter according to claim 1, wherein the metal impurities are at least one selected from the group consisting of Al, Ni, Fe, Cr, and Ti.
10. 10. A method for producing an ion-implanted silicon wafer, comprising the step of: injecting ions into a product silicon wafer using an ion implanter that has been evaluated as having a low level of metal contamination in step (D) by using the method for evaluating metal contamination in an ion implanter according to any one of claims 1 to 9 and determining that the concentration of the metal impurities measured in step (C) is below a lower detection limit.
Citation Information
Patent Citations
Method of measuring impurity quantity and manufacture of semiconductor device using the method
JP2000021803A
Metal contamination evaluating method, manufacturing method for semiconductor element, and electronic information equipment
JP2007258602A
Semiconductor epitaxial wafer manufacturing method, semiconductor epitaxial wafer and solid state imaging element manufacturing method
JP2015130402A
System and method for measuring contamination of ion implanter
JP1997180668A
Cited By
Tracing method and device for metal pollution of ion implanter
CN122238466A